Neospora then and now: prevalence of Neospora caninum in Maritime Canada in 1979, 1989, and 1998. - Keefe, G P (2000)
The seroprevalence of Neospora caninum was compared among New Brunswick, Nova Scotia, and Prince Edward Island in 1998, 1989, and 1979. In 1998, the seroprevalence was lowest in Prince Edward Island, where it was the same as in 1989. Neospora caninum was present in 1979, but at a lower prevalence.